Sensitivities in Satellite Lidar‐Derived Estimates of Daytime Top‐of‐the‐Atmosphere Optically Thin Cirrus Cloud Radiative Forcing: A Case Study. Issue 17 (10th September 2020) - Dolinar, Erica K.; Campbell, James R.; Lolli, Simone; Ozog, Scott C.; Yorks, John E.; Camacho, Christopher; Gu, Yu; Bucholtz, Anthony; McGill, Matthew J.
Abstract: An optically thin cirrus cloud was profiled concurrently with nadir‐pointing 1, 064 nm lidars on 11 August 2017 over eastern Texas, including NASA's airborne Cloud Physics Lidar (CPL) and space‐borne Clouds and Aerosol Transport System (CATS) instruments. Despite resolving fewer (37% vs. 94%) and denser (i.e., more emissive) clouds (average cloud optical depth of 0.10 vs. 0.03, respectively), CATS data render a near‐equal estimate of the top‐of‐atmosphere (TOA) net cloud radiative forcing (CRF) versus CPL. The sample‐relative TOA net CRF solved from CPL is 1.39 W/m 2, which becomes 1.32 W/m 2 after normalizing by occurrence frequency. Since CATS overestimates extinction for this case, the sample‐relative TOA net forcing is 3.0 W/m 2 larger than CPL, with the absolute value reduced to within 0.3 W/m 2 of CPL due its underestimation of cloud occurrence. We discuss the ramifications of thin cirrus cloud detectability from satellite and its impact on attempts at TOA CRF closure. Key Points: Coincident nadir 1, 064 nm lidar measurements of optically thin cirrus clouds were collected from aboard a high‐altitude aircraft and the International Space Station The relative top‐of‐the‐atmosphere (TOA) net cloud radiative forcing (CRF) solved from the two data sets reveal sensitivities to the algorithms used to derived cloud properties The absolute TOA net CRF solved from the two data sets are consistent despite limited cloud detection capabilities in the ISS product